Interior decorating in nineteenth-century France : the visual culture of a new profession - Lasc, Anca I. (Studies in design & material culture, 2018)
This volume explores the origins of interior design in 19th-century France. It shows how new, modern techniques of image-making and reproduction enabled the still-unnamed profession of the interior designer to take shape